The Effect of Team Game Tournament Teaching Method of Students’ Ability in Writing Procedure Text at The Ninth Grade of SMP Tamansiswa Pematangsiantar - Ramadhani, Madya; Maria Efipanias Manihuruk, Leonita; Lolo Siahaan, Basar; Hutahaean, David Togi (Innovative: Journal Of Social Science Research, 2024)
This research was conducted to assess the impact of the Team Game Tournament (TGT) teaching method on ninth-grade students' ability to write procedural texts at SMP Tamansiswa Pematangsiantar. A quasi-experimental design was employed, involving two classes with a total of 60 students. The researcher found that the mean post-test score for the experimental class was 80.8, while the control class scored a mean of 74.8. This indicates that the experimental class outperformed the control class. After analyzing the data, the researcher determined that the t-test value was greater than the t-table value (2.875>1.672). Therefore, it can be concluded that the TGT teaching method effectively enhances students' ability to write procedural texts at the ninth grade level at SMP Tamansiswa Pematangsiantar.